Trends in percutaneous left atrial appendage occlusion and 1-year mortality: a nationwide cohort study. (3rd October 2022) - Juhl Madsen, O; Lamberts, M K; Fosboel, E L; Gislason, G; Olesen, J B; Strange, J E
Abstract: Background: Percutaneous left atrial appendage occlusion (LAAO) is increasingly used for stroke prevention in high-risk patients with atrial fibrillation and contraindication for oral anticoagulation. However, studies evaluating comorbidities and mortality remain scarce. Objectives: The aim of this study was to evaluate changes in patient characteristic over time and 1-year risk of death. Methods: Using Danish nationwide registers, we included all patients undergoing first-time LAAO between 2013 and 2021. To evaluate changes in patient characteristics, the study population was stratified according to calendar year of LAAO procedure: 2013–2015, 2016–2018, and 2019–2021. Baseline patient characteristics were defined from 10 years prior to date of LAAO procedure. Antithrombotic therapy was defined as claimed prescriptions within 180 days prior to LAAO procedure. Patients were then followed until either emigration, death, one year of full follow-up, or end of study period. Baseline frailty risk was estimated with The Hospital Frailty Risk Score, a validated frailty risk assessment tool based on ICD-10 codes. The 1-year unadjusted risk of death was estimated with the Aalen-Johansen method. Results: In total, 1, 306 patients underwent LAAO. The number of LAAO increased from 201 procedures in 2013–2015 to 586 in 2019–2021. During follow-up, the age of the patients remained stable (2013–2015: median age: 70 years; 2016–2018: median age 69 years; 2019–2021: median age 69 years). Fewer patients had a history of ischemic stroke (2013–2015: 44.3% vs 2019–2021: 27.6%), hemorrhagic stroke (2013–2015: 32.8% vs 2019–2021: 21.0%), and previous bleeding (2013–2015: 71.1% vs 2019–2021: 59.2%). Median CHA2DS2-VASs score decreased over time (2013–2015: 4 vs 2019–2021: 3) and same trend was found in median HAS-BLED score (2013–2015: 3 vs 2019–2021: 2). In addition, fewer patients were categorized as high frailty risk (2013–2015: 16.9% vs 2019–2021: 8.9%). However, there was an increase in patients with a history of cancer (2013–2015: 11.9% vs 2019–2021: 18.9%). The use of antiplatelet therapy prior to LAAO decreased while the use of oral anticoagulation increased (2013–2015: 50.2% vs 2019–2021: 68.9%) due to a marked increase in non-vitamin K antagonist oral anticoagulants and a decrease in vitamin K antagonists (Figure 1). In total, 88 (7.22%) patients died within one year of LAAO procedure. The 1-year all-cause mortality risk in each period were similar (2013–2015: 7.0%; 2016–2018: 7.1%; 2019–2021: 6.9%). [Figure 2] Conclusion: In the years 2013–2021, the annual number of LAAO procedures increased. The age of patients remained stable. Comorbidity burden decreased and fewer patients were at high frailty risk, but the 1-year mortality risks were similar. Our real-life data suggest that profiles of patients undergoing LAAO has changed considerably over time. Funding Acknowledgement: Type of funding sources: None.